Impact of Vocational Education and Training On Decent Job Opportunities Regarding Information and Communication Technology - Do, Ha Thi Hai; Nguyen, Nui Dang; Pham, Toan Ngoc; Mai, Anh Ngoc; Le, Huong Thu Thi (Journal of Technical Education and Training, 2023)
Vocational education and training plays a crucial part in the creation of decent job. The fast growth of information and communication technology (ICT) during the past ten years has increased work opportunities for laborers. This research uses the yearly labor force survey data to study the impact of vocational education and training on decent job opportunities for employees in the context of Vietnam's information and communication technology development. The logit model results indicate that the 2020 rate of decent jobs is still low, at approximately 25.6 percent. However, vocational education and training and the advancement of ICT positively affect decent job opportunities. This long-lasting impact affects laborers in various areas, regions, and industries. These findings suggest that vocational education and training and ICT must play a significant role in transitioning from precarious to more secure employment, so laborers must acquire professional knowledge and information technology skills.